2018
DOI: 10.1016/j.amsu.2018.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Primary acinic cell carcinoma of the breast: A case report with a clinicopathological and immunohistochemical study of a rare breast cancer subtype

Abstract: Acinic cell carcinoma (ACC) of the breast is extremely rare subtype of triple-negative breast carcinoma and demonstrates extensive morphologic overlap with acinic cell carcinoma of the salivary gland. Herein, we report a case of acinic cell carcinoma of the breast in a 41-year old female presenting with a palpable breast mass along with significant morphological and immunohistochemical findings. Histologically, ACC showed a diffuse glandular infiltrative pattern, with small acinar or glandular structures mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Acinic cell carcinoma (ACC) of the breast is a subtype of TNBC, morphologically similar to ACC of the salivary glands ( Figure 1 A). It mainly affects adult women, presenting as a nodule/mass ranging in size from 10 to 52 mm (average 28 mm; summary in Supplementary Table S1 ) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Acinic Cell Carcinoma (Acc) Of the Breastmentioning
confidence: 99%
See 1 more Smart Citation
“…Acinic cell carcinoma (ACC) of the breast is a subtype of TNBC, morphologically similar to ACC of the salivary glands ( Figure 1 A). It mainly affects adult women, presenting as a nodule/mass ranging in size from 10 to 52 mm (average 28 mm; summary in Supplementary Table S1 ) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Acinic Cell Carcinoma (Acc) Of the Breastmentioning
confidence: 99%
“…ACC was originally described in 1996 [ 16 ], with a limited number of reported cases in the English literature. Foschini et al [ 41 ] listed 45 ACCs with a further 2 cases since reported [ 36 , 37 ]. Some studies include very limited or no follow-up data.…”
Section: Acinic Cell Carcinoma (Acc) Of the Breastmentioning
confidence: 99%
“… 0/2 49 Peritoneal metastases/DOD 2 Yu et al 3 (2022) [ 11 ] F/49 F/42 L uiq R uoq 35 30 Solid and microglandular Solid, microglandular and pseudolobular Mammography: Occult cancer. Mammography: Detected during screening 0/3 0/3 4 Waever et al (2021) [ 12 ] F/42 L 60 Solid, microlobular and pseudolobular Ultrasonography: Well-defined, lobulated, solid lesion with characteristics of a fibroadenoma 48 NED 5 Sen et al (2018) [ 13 ] F/41 R uoq 25 Acinar and solid Ultrasonography and mammography: No abnormalities. 0 12 NED 6 Li et al (2017) [ 14 ] F/52 L luq 15 Cystic and cribriform 0/1 3 AW 7 Kim et al 8 (2017) [ 15 ] 9 F/38 F/47 F/60 L L L 0 1a 0 NED NED NED 10 Kawai et al (2016) [ 16 ] F/49 R 35 Solid-trabecular and acinar Mammography: Lobulated mass...…”
Section: Introductionmentioning
confidence: 99%
“…Mammography revealed varieties of interpretations ranging from no abnormalities detected [ 11 ], occult carcinoma [ 15 ], a small oval radiopaque mass [ 16 ], a thickening with microcalcifications [ 17 ], a firm nodular lesion, a well-demarcated mass without microcalcifications to lobulated mass with poorly defined margins, without microcalcification, to a mass with well-defined margins with scattered granular calcifications [ 8 ]. Ultrasonography ranged from no abnormalities detected to a hypoechoic nodule with a smooth surface.…”
Section: Introductionmentioning
confidence: 99%